Indigenous Megaplatypus mutatus associated to wilting of Casuarina in Argentina - Ramos, Sergio Orlando; Ceriani Nakamurakare, Esteban; Gomez, Demian; Landi, Lucas (Unión Internacional de Organizaciones de Investigación Forestal (IUFRO), 2025)
Casuarina cunninghamiana (Australian pine) is adapted to a broad range of site conditions. In Argentina C. cunninghamiana is broadly used in ornamental gardens, groves guard for animals and windbreak in citrus plantations, reducing wind damage of fruit and preventing the spread of citrus canker (cancrosis). Wilting symptoms have been reported since 2007 without knowing the causal agent. In recent years the situation has worsened and many farms have completely lost their windbreaks.